Father Arsenie Papacioc and the Proper Arrangement of Spiritual Life. Glimpses of His Experiences in the Communist Prisons (Forum Theologicum Sardicense, 2025)
Father Arsenie Papacioc lived through numerous transformations of the Romanian nation, transitioning from the ‘fascination’ with the Legionary Movement to the ‘foolishness’ of monastic life. He experienced the prisons of various regimes in Romania, as well as the solitude of the wilderness, ultimately representing the life of the Orthodox Church before, during, and after communism. Consequently, Father Arsenie’s life is intertwined with the lives of many remarkable cultural, political, and especially ecclesial figures in Romanian history, from Patriarch Justinian to Archimandrites Cleopa Ilie and Ioanichie Bălan. His connections spanned numerous monasteries, including Cozia, Tismana (Cioclovina Skete), Sihăstria, Antim, Slatina, Neamț, Cheia, Căldărușani, Dintr-un Lemn, Cernica, and Techirghiol, as well as members of the Burning Bush Movement. His influence extended from a multitude of believers to hierarchs of the Romanian Orthodox Church, from the parish of Filea de Jos (and later Filea de Sus) to individuals of other religious denominations and convictions. Thus, Father Arsenie marked his epoch through the proper arrangement of his spiritual life to the measure of holiness, receiving many charismata from God glorified as the Holy Trinity.
Keywords: Arsenie Papacioc; Communist Regime; Spiritual Life; Orthodox Church; Monastic Life; The Burning Bush Movement